Synthesis of reactive faceted nanosized titania with enhanced photocatalytic performance under fluorine free conditions using deep eutectic solvent - Sandhu S.; Kumar N.; Singh V.P.; Singh V. (My University, 2025)
In this paper, we report a novel synthesis of nanosized anatase titania with exposed {001} and {111} highly reactive facets, using 1:3 M ratio of titanium butoxide (TBT) and choline chloride/hydroquinone (ChCl/Hq), a newly prepared deep eutectic solvent (DES) as a structure directing/capping agent along with variation in calcination temperature from 100ᵒC to 750ᵒC. The Rietveld refinement of XRD data of the lattice parameters of all samples indicated a sharp increase in O–Ti–O bond angle, indicating an increase in oxygen vacancies which could be attributed to the presence of highly exposed reactive facet which was further confirmed from the XPS analysis. The morphology evaluation from TEM/HRTEM of S3100 and S3350 confirmed the presence of {001} facet while a highly reactive {111} facet was observed in case of S3550. This work presents a greener approach for attaining the {111} reactive facet in anatase titania using DES replacing the toxic HF used in the previously reported studies. The photo-degradation studies of azo and anthraquinone based dyes with all catalysts were carried out and sample S3550 exhibited the multifold photoefficiency as compared to commercially available Degussa P-25 and synthesized {001} faceted S3100 and S3350 titania. © 2020